2019
DOI: 10.1186/s12905-019-0810-6
|View full text |Cite
|
Sign up to set email alerts
|

Fatalism in breast cancer and performing mammography on women with or without a family history of breast cancer

Abstract: Background Breast cancer is the most prevalent cancer in women, and in those with a positive family history, it is important to perform mammography. One of the probable barriers in doing mammography is fatalism. Methods This is a descriptive/cross-sectional study conducted on 400 women residing in Isfahan, Iran, randomly selected in 2017. Sampling was done randomly among the enrolled women in Health Integrity System. The data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…For example, medical history was indirectly associated with screening intention mediated through response cost, so there was a lower probability of mammography among women with a medical history. One possible explanation is that fatalism is more common in women with a medical history [ 52 ]. Previous studies have indicated that women with a family history of breast cancer or with a history of benign breast disease, who are more likely to believe in fatalism, may consider mammography an ineffective and high-cost screening method [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, medical history was indirectly associated with screening intention mediated through response cost, so there was a lower probability of mammography among women with a medical history. One possible explanation is that fatalism is more common in women with a medical history [ 52 ]. Previous studies have indicated that women with a family history of breast cancer or with a history of benign breast disease, who are more likely to believe in fatalism, may consider mammography an ineffective and high-cost screening method [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that fatalism is more common in women with a medical history [ 52 ]. Previous studies have indicated that women with a family history of breast cancer or with a history of benign breast disease, who are more likely to believe in fatalism, may consider mammography an ineffective and high-cost screening method [ 52 , 53 , 54 ]. This may also explain the positive association between medical history and response cost, suggesting that in addition to PMT subconstructs, breast cancer screening programs might also benefit by considering these socio-demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with cancer fatalistic beliefs, which claim that an external force controls all events or actions in a person's life [ 20 ]. An inverse relationship between cancer fatalistic attitudes and mammography uptake has been observed in the literature [ 21 , 22 ]. This finding emphasises the significance of further investigating Palestinian women's perceived cancer fatalistic attitudes and discussing them as part of cancer prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer fatalism is a set of attitudes and behaviours that suggest cancer screening and treatment is futile and disease prevention is beyond human control [17,76,[93][94][95]. Researchers believe that the link between cancer and fatalism results from poverty, low education and old age [95,96], and is also higher in people with no history of mammography [69]. Women in many Asian countries believe that death and life are our fate, which cannot be changed.…”
Section: -11 Fatalismmentioning
confidence: 99%